The Mesozoic Caosiyao giant porphyry Mo deposit in Inner Mongolia, North China and Paleo-Pacific subduction-related magmatism in the northern North China Craton. (1st September 2016) - Wu, Huaying; Zhang, Lianchang; Pirajno, Franco; Shu, Qihai; Zhang, Min; Zhu, Mingtian; Xiang, Peng
Graphical abstract: Highlights: The Caosiyao giant porphyry Mo deposit formed during 147–150 Ma. Host granitoids are silica and alkali rich, highly oxidized and differentiated. Host granitoids show crustal component as envisaged by high negative εHf ( t ) values. Mo mineralization was associated with an extensional tectonic setting. It was caused by far-field tectonics related to the Paleo-Pacific subduction. Abstract: The Caosiyao giant porphyry Mo deposit is located in the Wulanchabu area of Inner Mongolia, within the northern North China Craton (NCC). It contains more than 2385 Mt of ore with an average grade of 0.075% Mo. In the Caosiyao mining district, Mo mineralization occurs mainly in a Mesozoic granite porphyry as disseminations and stockworks, with some Mo distributed in Archean metamorphic rocks and diabase as stockworks and veins. The host granite porphyry is composed of two different phases that can be distinguished based on mineral assemblages and textures: one phase contains large and abundant phenocrysts (coarse-grained), while the other phase is characterized by fewer and smaller phenocrysts (medium-grained). Zircon U–Pb–Hf analyses of the former phase yielded a concordant 206 Pb/ 238 U age of 149.8 ± 2.4 Ma with a 206 Pb/ 238 U weighted mean age of 149.9 ± 2.4 Ma and εHf ( t ) values ranging from −12.2 to 18.3, while the latter phase gave a concordant 206 Pb/ 238 U age of 149.0 ± 2.2 Ma with a 206 Pb/ 238 U weighted mean age of 149.0 ± 2.1 Ma and εHf ( t ) values ranging from −13.1 to 17.7. Five samples of disseminated molybdenite have a 187 Re– 187 Os isochron age of 149.5 ± 5.3 Ma with a weighted average age of 149.0 ± 1.8 Ma, whereas six veinlet-type molybdenite samples have a well-constrained 187 Re– 187 Os isochron age of 146.9 ± 3.1 Ma and a weighted average age of 146.5 ± 0.8 Ma. Thus, it is suggested that the Mo mineralization of the Caosiyao deposit occurred during the Late Jurassic (ca. 147–149 Ma), almost coeval with the emplacement of the host granite porphyry (ca. 149–150 Ma). The host granite porphyry is characterized by high silica (SiO2  = 71.52–74.10 wt%), relatively high levels of oxidation (Fe2 O3 /FeO = 0.32–0.94 wt%) and high alkali element concentrations (Na2 O + K2 O = 8.21–8.76 wt%). The host granite porphyry also shows enrichments in U and K, and depletion in Ba, Sr, P, Eu, and Ti, suggesting strong fractional crystallization of plagioclase, biotite, and accessory minerals. These observations, together with high SiO2 contents and a high differentiation index (DI = 89.04–92.44), indicate a strong differentiation of the granite magma. Based on geological, geochronological, isotope systematics, and geochemical studies, we propose, for the first time, a genetic model for the Caosiyao porphyry Mo deposit. Under a regional extensional setting caused by far-field tectonics related to the Paleo-Pacific subduction during the Late Jurassic, a series of geodynamic, magmatic, and ore-forming processes took place, including formation of multi-directional and multi-phase faults, emplacement of the granitic host rocks, and Mo mineralization. Highly silicic, highly oxidized, and alkali-rich granitic magma, derived from partial melting of old lower crust, intruded into the country rocks. This highly differentiated granitic magma and the exsolved ore-forming fluids, enriched in Mo, migrated upward and interacted with the wall rocks. Eventually, ore minerals precipitated in fractures, resulting in the extensive deposition of molybdenite.